Cultural narrative, crisis, and contention in Iceland's bid to join the European Union, 2009–2015 - Hallgrímsdóttir, Helga Kristín; Carpenter, Michael J.; Brunet-Jailly, Emmanuel; Conrad, Maximilian (Frontiers in Political Science, 2024)
In the wake of the 2008 global financial crisis, Iceland launched a bid to join the European Union. Joining the EU was presented domestically as a key to economic recovery and as a preventative measure against future economic distress. The bid itself was framed within a rapidly shifting political landscape, set against a backdrop of spreading economic malaise across Europe, accompanied by economic bailout plans and austerity measures. Several aspects of the bid’s ultimate failure demonstrate the importance of identities and narratives around national independence and European integration. Most saliently, widespread perceptions about what it would mean to join the EU, particularly around sensitive notions of sovereignty, proved insurmountable to the more economistic rationale of the pro-EU campaign. The Icelandic bid thus presents a distinct opportunity to drill down into the complex relationships between austerity economics, popular politics, and the European integration project, with significant policy implications. To better understand the emergence of the bid and its failure in sociopolitical terms we assess different conceptual frameworks, including functionalist, intergovernmentalist, and post-functionalist approaches and theoretical perspectives on crisis and contentious politics. We also include voices of Icelandic citizens from civil society and government collected in research interviews between 2012 and 2018. Overall, our comparative theoretical approach and original case data sharpen an emphasis in the social sciences and policy research on the importance of cultural narrative and identity as key determinants of EU integration.